ALIGNING ORGANIZATIONAL STRATEGY FOR MAINTENANCE 4.0: A McKINSEY 7S ANALYSIS OF MRT JAKARTA’S RAILWAY INFRASTRUCTURE MAINTENANCE DIGITAL TRANSFORMATION - Irham Ahmadirizka; Gatot Yudoko (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This paper is researching on the readiness of MRT Jakarta’s Railway Infrastructure Maintenance (RIM) Division to improve its level of maintenance, through alignment of organizational strategy with digital transformation. The reliability of equipment is the key for successful Urban Metro, therefore MRT Jakarta is looking to transition from reactive and preventive to predictive, data-driven maintenance. Drawing on the McKinsey 7S framework with Maintenance Digital Transformation (MDT) elements, the research assesses digital readiness in seven dimensions: Strategy, Structure, Systems, Shared Values, Skills, Style, and Staff. A mixed-method approach was adopted, including quantitative surveys and qualitative interviews to determine maturity and pinpoint key areas of weakness. Findings indicate moderate maturity in the majority of dimensions, areas of weakness found in digital system integration, leadership commitment, and staff skills. The paper outlines the Digital Transformation Acceleration Program (DTAP), the structured guide that highlights system automation, integration between departments, and digital competency building. The findings highlight that digital transformation is not merely about technological improvements but demands overall synergy of human, technical, and strategic resources. The study provides tangible insights into action for public infrastructure agencies looking to upgrade maintenance functions and realign internal capabilities to new digital standards.